1997
DOI: 10.1021/jf960780o
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of α-Farnesene and Its Conjugated Trienol Oxidation Products from Apple Peel by C18-HPLC with UV Detection

Abstract: Conjugated triene oxidation products of the sesquiterpene α-farnesene are thought to induce development of the storage disorder superficial scald. A C18-HPLC method was devised which allows simultaneous quantification of α-farnesene and its major oxidation product, a conjugated trienol, in hexane extracts of apple peel using UV detection at 232 and 269 nm. Identification of the compounds was confirmed by UV spectrometry, HPLC with diode array detection, and GC−MS. Apples of high (Granny Smith, GS), moderate (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
66
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(83 citation statements)
references
References 13 publications
16
66
0
1
Order By: Relevance
“…Effectively, the increase of TC in this treatment began in month 2 and was distinct from the other treatments until the end of the storage period. This affirms the theory that identifies AF as the indirect precursor of superficial scald and the results are in agreement with those described by several authors (Huelin and Coggiola, 1968;Barden and Bramlage, 1994;Whitaker et al, 1997;Shaham et al, 2003). Gradual cooling of the fruit by itself resulted in reducing AF accumulation beginning at 30 days of storage; this lower availability of AF could be responsible for the drastic reduction in scald that was observed in this treatment (1.3%).…”
Section: Chemical Compounds and The Incidence Of Superficial Scaldsupporting
confidence: 93%
See 1 more Smart Citation
“…Effectively, the increase of TC in this treatment began in month 2 and was distinct from the other treatments until the end of the storage period. This affirms the theory that identifies AF as the indirect precursor of superficial scald and the results are in agreement with those described by several authors (Huelin and Coggiola, 1968;Barden and Bramlage, 1994;Whitaker et al, 1997;Shaham et al, 2003). Gradual cooling of the fruit by itself resulted in reducing AF accumulation beginning at 30 days of storage; this lower availability of AF could be responsible for the drastic reduction in scald that was observed in this treatment (1.3%).…”
Section: Chemical Compounds and The Incidence Of Superficial Scaldsupporting
confidence: 93%
“…The greatest synthesis of AF occurred in fruit with normal cooling without 1-MCP ( Figure 2B), reaching the maximum concentration at 60 days of storage, product of its oxidation into TC (Huelin and Coggiola, 1968;Meir and Bramlage, 1988;Whitaker et al, 1997;Pechous et al, 2005). Effectively, the increase of TC in this treatment began in month 2 and was distinct from the other treatments until the end of the storage period.…”
Section: Chemical Compounds and The Incidence Of Superficial Scaldmentioning
confidence: 85%
“…From the viewpoint of postharvest practice, α-farnesene metabolism may be a manipulating point to control superficial scald, a major physiological disorder in apples and pears (Ju and Curry, 2000;Isidoro and Almeida, 2006). The reactive conjugated trienols resulting from the in vivo oxidation of α-farnesene are believed to be directly responsible for primary events leading to development of superficial scald (Rowan et al, 1995;Whitaker et al, 1997). In our experiment, the accumulations of α-farnesene and conjugated trienols in control fruits had accumulating peaks during storage, and the peaks of conjugated trienols were always later than that of α-farnesene (Figure 5), which meant that α-farnesene fluctuation was followed by the accumulation of conjugated trienols.…”
Section: Discussionmentioning
confidence: 99%
“…The compound eluted after 61.2 min, encompassing 57.0% of the total peak area, contained molecule fragments corresponding to spectrums for α-farnesene published previously (Rowan et al 1995;Whitaker et al 1997;Rudell et al 2009). The odour of α-farnesene has been characterised as freshly green and herbaceous (Arvisenet et al 2008).…”
Section: Resultsmentioning
confidence: 87%
“…The compound eluted after 53.7 min, encompassing 1.0% of the total peak area, (minor variant) and the compound eluted after 40.0 min, with a peak area of 7% (major variant), had a characteristic spectra pattern for 2,6,10-trimethyldodeca-2,7E,9E,11-tetraen-6-ol and its Z-isomer 2,7E,9Z,11 (Rowan et al 1995;Whitaker et al 1997;Fielder et al 1998;Krings et al 2006;Whitaker 2007). In this research the peak area of the major variant was seven times higher in comparison to the peak area of the minor variant, while Whitaker et al (2007) found that the level of the major variant was 10 times higher in comparison to the minor variant.…”
Section: Resultsmentioning
confidence: 99%